Primary school students and climate change–an interview study in Finland and Tanzania. (20th December 2022) - Sjöblom, Pia; Wolff, Lili-Ann; Vuorenpää, Sari; Grahn, Rebecka
Abstract: Climate change is a complex and wicked problem, which needs to be addressed through relevant climate change education. However, the preconditions for combatting climate change differ in different parts of the world, depending on physical, cultural and social circumstances. The diversity of circumstances also influences the implementation of climate change in education. Therefore, in this article we have chosen to examine climate change education (CCE) based on an interview study in two distinct school contexts. More specifically, the cases aim to explore Finnish and Tanzanian primary students' views on climate change. A hermeneutical approach guided the analysis, and a significant result was that most of the students understood the severity of climate change. Nevertheless, some misconceptions regarding both causes, consequences and mitigation of climate change were also obvious. In addition, the analysis revealed interesting variations in the students' reasoning, which relate to their different contexts. Unquestionably, the sample size in this study is limited, and further research is needed for a more detailed picture of Finnish and Tanzanian students' views.